Elderly Care Ethics: A Glance on Principlism - Nurunnabi, Abu Sadat Mohammad; Tanira, Shaorin; Sony, Sadia Akther (Bangladesh Journal of Bioethics, 2016)
Being a low-income country of South Asia region, Bangladesh has been struggling with its health budget for increasing elderly population over the decades. However, concerns regarding the aging population and its impact on countrys socio-economic status have come to the forefront in the policy making and implementation towards national development in recent years. This paper is intended to discuss ethical issues, in context of principlism, that are likely to arise and the means to deal with ethical dilemmas in healthcare of elderly people involving seniors themselves and their service providers whether professionals or family members. To provide the highest level of care, the entire caregiving team needs to form a partnership having the best interest of the elderly people as their focal point while providing loving, appropriate care to enhance their quality of care, their quality of life and their happiness in the latter days of their lives which is coined as healthy ageing.